PREPARATION OF OXIDE SUPERCONDUCTING YBa2Cu3O7-x BY SOL-GEL METHOD - Bustamante, A. (2004)
We present the synthesis of YBa2Cu3O7-x superconductor oxide with critical temperature - 92 K, by Sol-Gel method. The synthesis of this superconducting compound was performed by using oxalate precursor solution which were prepared by dissolving stoichiometric mixtures of the Y(OOCCH3)•4H2O; Ba(OOCCH3)2 and Cu(OOCCH3)2•H2O acetates in an aqueous solution of oxalic acid, HCOO-COOH. The gel obtained was calcined at 860 oC and then fired at 920 oC in oxidizing atmosphere. The characterization of this superconducting ceramic was performed by x-ray diffraction, micro-Raman spectroscopy and SQUID techniques.